Large-size quartz crucible and preparation method thereof

By adding a zirconia/silicon carbon composite material layer to the opaque layer of the large-sized quartz crucible and applying high-temperature resistant coating to the inner wall of the transparent layer, the problem of large-sized quartz crucibles being easily deformed or broken at high temperature is solved, and the mechanical strength and thermal shock resistance are enhanced, the service life is extended and the high temperature and corrosion resistance are maintained.

CN119504243APending Publication Date: 2025-02-25JIANGSU XINYUDA NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411601065.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Large-sized quartz crucibles are prone to deformation or cracking at high temperatures, resulting in reduced structural stability and shortened service life.

Method used

The zirconia/silicon carbon composite material layer is added to the opaque layer of the quartz crucible and a high-temperature resistant coating is coated on the inner wall of the transparent layer. This method enhances the mechanical strength and thermal shock resistance of the crucible.

Benefits of technology

It effectively enhances the mechanical strength and thermal shock resistance of the quartz crucible, so that it has sufficient structural stability under large sizes, extends its service life, and maintains excellent high temperature and corrosion resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a large-size quartz crucible, and particularly relates to the technical field of quartz crucibles. A zirconium oxide / silicon carbon composite material layer is added on a non-transparent layer of the quartz crucible, so that the mechanical strength and thermal shock resistance of the crucible are effectively enhanced, and the crucible still has enough structural stability under the large-size condition; the design of the transparent layer not only ensures the light transmission and heat resistance of the crucible, but also provides additional strength support for the crucible after the size of the crucible is expanded, so that the crucible can still maintain excellent high temperature resistance and corrosion resistance when the size of the crucible is expanded to 30-44 inches, and the requirements of the stability and the service life of the large-size quartz crucible during use are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quartz crucibles, and in particular to a large-sized quartz crucible and a preparation method thereof. Background Art

[0002] Quartz crucible is a container made of high-purity quartz material, which is widely used in semiconductor, photovoltaic, chemical experiment and other fields. Since quartz has an extremely high melting point and good chemical stability, quartz crucible can be used under high temperature conditions and does not react with most substances. Quartz crucible has strong resistance to thermal shock and can be quickly heated and cooled to ensure the safety and reliability of the experimental process. It is an important instrument commonly used in laboratories and industrial production.

[0003] The size of conventional quartz crucibles is generally 12-28 inches, while the mechanical strength of quartz crucibles larger than 30 inches is often difficult to meet the requirements of high-temperature working environments. Crucibles are prone to deformation or cracking at high temperatures because as the size of the crucible increases, the effects of uneven heating and thermal stress will intensify, resulting in a decrease in structural stability and ultimately shortening its service life. Summary of the invention

[0004] The object of the present invention is to provide a large-sized quartz crucible and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a large-sized quartz crucible, comprising the following steps:

[0006] S1. Put quartz sand, binder and reinforcing material into a mixer in a ratio of 8:1.5:0.5 and mix them for about 20-30 minutes, and add deionized water to obtain an opaque layer mixture;

[0007] S2. Press the opaque layer mixture into shape using a pressing device, apply a pressure of 35 MPa, hold for 2 minutes, then demould and dry naturally to obtain an opaque layer with a thickness of 5-6 mm;

[0008] S3, coating a zirconium oxide / silicon carbon composite material layer on the opaque layer and drying it naturally, with the thickness controlled at 4-5 mm, to obtain a composite reinforcement layer;

[0009] S4, putting the quartz powder and the binder into a blender in a ratio of 9:1 and mixing them for about 20-30 minutes and adding deionized water to obtain a transparent layer mixture;

[0010] S5, coating the transparent layer mixture evenly on the surface of the composite reinforcement layer and drying it naturally, with the thickness controlled at 3-4 mm, to obtain an initial quartz crucible;

[0011] S6, placing the initial crucible in a high temperature furnace for sintering, and naturally cooling to room temperature, controlling the cooling rate within 20°C / h, to obtain a quartz crucible;

[0012] S7. Apply a high temperature resistant coating to the inner wall of the transparent layer of the quartz crucible to form a coating with a thickness of about 2 mm.

[0013] Preferably, in S3, the preparation of the composite reinforcement layer comprises the following steps:

[0014] S31, putting zirconium oxide powder and silicon carbon powder into a ball mill in a ratio of 7:3 and uniformly mixing them for 3 hours to obtain a mixture;

[0015] S32, grinding the inner wall of the naturally dried opaque layer to make it smooth without obvious bumps;

[0016] S33, use injection equipment to apply the mixture on the opaque layer, and spread it evenly with a roller, with the thickness controlled at 5-10mm.

[0017] Preferably, in S2, a release agent is applied on the surface of the mold, and the release agent is graphite powder.

[0018] Preferably, in S1 and S4, the particle size of the quartz sand is 80-100 mesh, and the particle size of the binder is less than 100 mesh.

[0019] Preferably, in S1 and S4, the water content of the mixture in the mixer is between 5-7%.

[0020] Preferably, in S1 and S4, the purity of the quartz sand and quartz powder is ≥99.998%.

[0021] Preferably, in S6, the temperature in the furnace is set to be above 1600°C, and the temperature is increased in stages and maintained at a constant temperature for 2-4 hours.

[0022] Preferably, in S7, the high temperature resistant coating is a silicate coating.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention adds a zirconium oxide / silicon carbon composite material layer to the opaque layer of the quartz crucible, which effectively enhances the mechanical strength and thermal shock resistance of the crucible, so that it still has sufficient structural stability when it is large in size. The design of the transparent layer not only ensures the light transmittance and heat resistance of the crucible, but also provides additional strength support for the crucible after the size is expanded, so that the crucible can maintain excellent high temperature resistance and corrosion resistance when the size is expanded to 30-44 inches, thereby meeting the stability and service life of large-sized quartz crucibles when in use. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] A specific embodiment of the present invention provides a large-sized quartz crucible and a preparation method thereof, comprising the following steps:

[0026] S1. Put quartz sand, binder and reinforcing material into a mixer in a ratio of 8:1.5:0.5 and mix them for about 20-30 minutes, and add deionized water to obtain an opaque layer mixture;

[0027] S2. Press the opaque layer mixture into shape using a pressing device, apply a pressure of 35 MPa, hold for 2 minutes, then demould and dry naturally to obtain an opaque layer with a thickness of 5-6 mm;

[0028] The mold release agent is applied on the mold surface for mold release treatment, and the mold release agent is graphite powder.

[0029] S3, coating a zirconium oxide / silicon carbon composite material layer on the opaque layer and drying it naturally, with the thickness controlled at 4-5 mm, to obtain a composite reinforcement layer;

[0030] S4, putting the quartz powder and the binder into a mixer in a ratio of 9:1 and mixing them for about 20-30 minutes and adding deionized water to obtain a transparent layer mixture;

[0031] S5, coating the transparent layer mixture evenly on the surface of the composite reinforcement layer and drying it naturally, with the thickness controlled at 3-4 mm, to obtain an initial quartz crucible;

[0032] S6, placing the initial crucible in a high temperature furnace for sintering, and naturally cooling to room temperature, controlling the cooling rate within 20°C / h, to obtain a quartz crucible;

[0033] The temperature in the furnace is set at above 1600°C, and the temperature is increased in stages to maintain a constant temperature for 2-4 hours.

[0034] S7. Apply a high temperature resistant coating to the inner wall of the transparent layer of the quartz crucible to form a coating with a thickness of about 2 mm.

[0035] Specifically, in S1 and S4, the particle size of the quartz sand is 80-100 mesh, the particle size of the binder is less than 100 mesh, the water content of the mixture in the mixer is between 5-7%, and further, the purity of the quartz sand and the quartz powder is ≥99.998%.

[0036] Embodiment 1

[0037] This embodiment provides a large-sized quartz crucible and a preparation method thereof, comprising the following steps:

[0038] S1. Put quartz sand, binder and reinforcing material into a mixer in a ratio of 8:1.5:0.5, mix them for about 20 minutes and add deionized water to obtain an opaque layer mixture;

[0039] S2, using a pressing device to press the opaque layer mixture into shape, applying a pressure of 35 MPa, maintaining for 2 minutes, demolding and naturally drying, to obtain an opaque layer with a thickness of 5 mm;

[0040] S3, coating a zirconium oxide / silicon carbon composite material layer on the opaque layer and drying it naturally, with the thickness controlled at 5 mm, to obtain a composite reinforcement layer;

[0041] S4, putting the quartz powder and the binder into a mixer in a ratio of 9:1 and mixing them for about 20 minutes and adding deionized water to obtain a transparent layer mixture;

[0042] S5, coating the transparent layer mixture evenly on the surface of the composite reinforcement layer and drying it naturally, with the thickness controlled at 3 mm, to obtain an initial quartz crucible;

[0043] S6, placing the initial crucible in a high temperature furnace for sintering, and naturally cooling to room temperature, controlling the cooling rate within 20°C / h, to obtain a quartz crucible;

[0044] S7. Apply a high temperature resistant coating to the inner wall of the transparent layer of the quartz crucible to form a coating with a thickness of about 2 mm.

[0045] Embodiment 2

[0046] This embodiment provides a large-sized quartz crucible and a preparation method thereof, comprising the following steps:

[0047] S1. Put quartz sand, binder and reinforcing material into a mixer in a ratio of 8:1.5:0.5, mix them for about 20 minutes and add deionized water to obtain an opaque layer mixture;

[0048] S2, using a pressing device to press the opaque layer mixture into shape, applying a pressure of 35 MPa, maintaining for 2 minutes, demolding and naturally drying, to obtain an opaque layer with a thickness of 6 mm;

[0049] S3, coating a zirconium oxide / silicon carbon composite material layer on the opaque layer and drying it naturally, with the thickness controlled at 5 mm, to obtain a composite reinforcement layer;

[0050] S4, putting the quartz powder and the binder into a mixer in a ratio of 9:1 and mixing them for about 20 minutes and adding deionized water to obtain a transparent layer mixture;

[0051] S5, coating the transparent layer mixture evenly on the surface of the composite reinforcement layer and drying it naturally, with the thickness controlled at 4 mm, to obtain an initial quartz crucible;

[0052] S6, placing the initial crucible in a high temperature furnace for sintering, and naturally cooling to room temperature, controlling the cooling rate within 20°C / h, to obtain a quartz crucible;

[0053] S7. Apply a high temperature resistant coating to the inner wall of the transparent layer of the quartz crucible to form a coating with a thickness of about 2 mm.

[0054] Embodiment 3

[0055] This embodiment provides a large-sized quartz crucible and a preparation method thereof, comprising the following steps:

[0056] S1. Put quartz sand, binder and reinforcing material into a mixer in a ratio of 8:1.5:0.5, mix them for about 20 minutes and add deionized water to obtain an opaque layer mixture;

[0057] S2, using a pressing device to press the opaque layer mixture into shape, applying a pressure of 35 MPa, maintaining for 2 minutes, demolding and naturally drying, to obtain an opaque layer with a thickness of 6 mm;

[0058] S3, coating a zirconium oxide / silicon carbon composite material layer on the opaque layer and drying it naturally, with the thickness controlled at 5 mm, to obtain a composite reinforcement layer;

[0059] S4, putting the quartz powder and the binder into a blender in a ratio of 9:1 and mixing them for about 20 minutes, and adding deionized water to obtain a transparent layer mixture;

[0060] S5, coating the transparent layer mixture evenly on the surface of the composite reinforcement layer and drying it naturally, with the thickness controlled at 3 mm, to obtain an initial quartz crucible;

[0061] S6, placing the initial crucible in a high temperature furnace for sintering, and naturally cooling to room temperature, controlling the cooling rate within 20°C / h, to obtain a quartz crucible;

[0062] S7. Apply a high temperature resistant coating to the inner wall of the transparent layer of the quartz crucible to form a coating with a thickness of about 2 mm.

[0063] Embodiment 4

[0064] This embodiment provides a large-sized quartz crucible and a preparation method thereof, comprising the following steps:

[0065] S1. Put quartz sand, binder and reinforcing material into a mixer in a ratio of 8:1.5:0.5 and mix them for about 20 minutes, and add deionized water to obtain an opaque layer mixture;

[0066] S2, using a pressing device to press the opaque layer mixture into shape, applying a pressure of 35 MPa, maintaining for 2 minutes, demolding and naturally drying, to obtain an opaque layer with a thickness of 5 mm;

[0067] S3, coating a zirconium oxide / silicon carbon composite material layer on the opaque layer and drying it naturally, with the thickness controlled at 4 mm, to obtain a composite reinforcement layer;

[0068] S4, putting the quartz powder and the binder into a blender in a ratio of 9:1 and mixing them for about 20 minutes, and adding deionized water to obtain a transparent layer mixture;

[0069] S5, coating the transparent layer mixture evenly on the surface of the composite reinforcement layer and drying it naturally, with the thickness controlled at 3 mm, to obtain an initial quartz crucible;

[0070] S6, placing the initial crucible in a high temperature furnace for sintering, and naturally cooling to room temperature, controlling the cooling rate within 20°C / h, to obtain a quartz crucible;

[0071] S7. Apply a high temperature resistant coating to the inner wall of the transparent layer of the quartz crucible to form a coating with a thickness of about 2 mm.

[0072] Comparative experiment: The quartz crucible prepared by the large-size quartz crucible and the preparation method thereof provided in Examples 1 to 4 was tested for service life, whether sintering cracked, compressive strength, corrosion resistance, and high temperature resistance. The test data are as follows:

[0073] Table 1 is the quartz crucible performance test record:

[0074] Test items Embodiment 1 Embodiment 2 Embodiment 3 Embodiment 4 Duration of use (h) 500 600 520 580 Sintering conditions No cracking No cracking Slight cracking No cracking Compressive strength(MPa) 88 90 87 88 Corrosion resistance excellent excellent good excellent High temperature resistance(℃) 1750 1800 1750 1780

[0075] According to the results of the quartz crucible performance test record table in Table 1, it can be learned that the quartz crucible prepared in Example 2 performed best in all tests, and was outstanding in terms of service life, compressive strength, high temperature resistance and thermal shock stability, and was suitable for use under extreme conditions. The quartz crucible prepared in Example 4 had excellent comprehensive performance, a long service life, and its compressive strength and thermal shock stability were also close to those of Example 2, and was suitable as a suboptimal choice. The quartz crucible prepared in Example 1 had stable overall performance and was suitable for use in conventional high temperature environments. The quartz crucible prepared in Example 3 was slightly insufficient in terms of compressive strength and thermal shock stability, and was suitable for use in occasions with low environmental requirements.

[0076] In summary: the present invention adds a zirconium oxide / silicon carbon composite material layer to the opaque layer of the quartz crucible, which effectively enhances the mechanical strength and thermal shock resistance of the crucible, so that it still has sufficient structural stability when it is large in size. The design of the transparent layer not only ensures the light transmittance and heat resistance of the crucible, but also provides additional strength support for the crucible after the size is expanded, so that the crucible can be expanded to 30-44 inches in size while still maintaining excellent high temperature resistance and corrosion resistance, thereby meeting the stability and service life of large-sized quartz crucibles when used.

[0077] Parts not involved in the present invention are the same as the prior art or can be implemented by the prior art. Although the embodiments of the present invention have been shown and described, it is understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a large-sized quartz crucible, characterized in that: The following steps are involved: S1. Put quartz sand, binder and reinforcing material into a mixer in a ratio of 8:1.5:0.5 and mix them for about 20-30 minutes, and add deionized water to obtain an opaque layer mixture; S2. Press the opaque layer mixture into shape using a pressing device, apply a pressure of 35 MPa, hold for 2 minutes, then demould and dry naturally to obtain an opaque layer with a thickness of 5-6 mm; S3, coating a zirconium oxide / silicon carbon composite material layer on the opaque layer and drying it naturally, with the thickness controlled at 4-5 mm, to obtain a composite reinforcement layer; S4, putting the quartz powder and the binder into a blender in a ratio of 9:1 and mixing them for about 20-30 minutes and adding deionized water to obtain a transparent layer mixture; S5, coating the transparent layer mixture evenly on the surface of the composite reinforcement layer and drying it naturally, with the thickness controlled at 3-4 mm, to obtain an initial quartz crucible; S6, placing the initial crucible in a high temperature furnace for sintering, and naturally cooling to room temperature, controlling the cooling rate within 20°C / h, to obtain a quartz crucible; S7. Apply a high temperature resistant coating to the inner wall of the transparent layer of the quartz crucible to form a coating with a thickness of about 2 mm.

2. The method for preparing a large-sized quartz crucible according to claim 1, characterized in that: In S3, the preparation of the composite reinforcement layer comprises the following steps: S31, putting zirconium oxide powder and silicon carbon powder into a ball mill in a ratio of 7:3 and uniformly mixing them for 3 hours to obtain a mixture; S32, grinding the inner wall of the naturally dried opaque layer to make it smooth without obvious bumps; S33, use injection equipment to apply the mixture on the opaque layer, and spread it evenly with a roller, with the thickness controlled at 5-10mm.

3. The method for preparing a large-sized quartz crucible according to claim 1, characterized in that: In S2, a release agent is applied on the surface of the mold, and the release agent is graphite powder.

4. The method for preparing a large-sized quartz crucible according to claim 1, characterized in that: In the S1 and S4, the particle size of the quartz sand is 80-100 meshes, and the particle size of the binder is less than 100 meshes.

5. The method for preparing a large-sized quartz crucible according to claim 1, characterized in that: In the S1 and S4, the water content of the mixture in the mixer is between 5% and 7%.

6. The method for preparing a large-sized quartz crucible according to claim 1, characterized in that: In the S1 and S4, the purity of the quartz sand and the quartz powder is ≥99.998%.

7. The method for preparing a large-sized quartz crucible according to claim 1, characterized in that: In S6, the temperature in the furnace is set to be above 1600°C, and the temperature is increased in stages to maintain a constant temperature for 2-4 hours.

8. The method for preparing a large-sized quartz crucible according to claim 1, characterized in that: In S7, the high temperature resistant coating is silicate coating.

9. A large-sized quartz crucible, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.